2018
DOI: 10.1186/s12894-018-0362-3
|View full text |Cite
|
Sign up to set email alerts
|

Decolonization potential of 0.02% polyhexanide irrigation solution in urethral catheters under practice-like in vitro conditions

Abstract: BackgroundLong-term use of indwelling urethral catheters is associated with high risk of urinary tract infection (UTI) and blockage, which may in turn cause significant morbidity and reduce the life of the catheter. A 0.02% polyhexanide irrigation solution has been developed for routine mechanical rinsing together with bacterial decolonization of suprapubic and indwelling urethral catheters.MethodsUsing a practice-like in vitro assay and standard silicon catheters, artificially contaminated with clinically rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Although the foreseen number of participants has not been reached, the data from this study, combined with the clinical and preclinical data available for polihexanide, demonstrate sufficient evidence that the substance can safely be used for catheter irrigation. An initial in vitro study using a polihexanide solution in bladder catheters has already demonstrated bactericidal activity, leading to bacterial decolonization of the catheters (22). Future studies should evaluate its clinical effectiveness in patients with long-term indwelling catheters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the foreseen number of participants has not been reached, the data from this study, combined with the clinical and preclinical data available for polihexanide, demonstrate sufficient evidence that the substance can safely be used for catheter irrigation. An initial in vitro study using a polihexanide solution in bladder catheters has already demonstrated bactericidal activity, leading to bacterial decolonization of the catheters (22). Future studies should evaluate its clinical effectiveness in patients with long-term indwelling catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 28 reported AEs, 22 (78.6%) were classified as Adverse Device Effects (ADEs). For these 22 ADEs, the association between the AEs and the medical device was classified as possible (n = 16;…”
Section: Patient Demographics and Baseline Characteristicsmentioning
confidence: 99%
“…Medical devices such as suprapubic and indwelling catheters used in clinical settings are frequently colonized by bio lms of a variety of microbial species with detrimental consequences for the patients (13). Research is focused on decolonization of urethral catheters via treatment with a range of systemic antibiotic regimens (14) even though antibiotic resistance and drug adsorption are heavily modi ed in bio lms (4,6,13). In fact, antimicrobial compounds are usually not able to penetrate the full depth of the microbial bio lms, reducing the available options for effective therapy (15).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogens such as Escherichia coli, Enterobacter spp., Pseudomonas spp., Enterococcus spp., Staphylococcus aureus, coagulase-negative staphylococci and yeasts are common causes of urinary tract infections and catheter blockage (4,6) and the most commonly reported species forming bio lms on urethral catheters are Candida spp., Pseudomonas aeruginosa, Proteus mirabilis, E. faecalis, and S. aureus (2,4). Scanning electron microscopy performed on bio lms formed on indwelling catheters has shown depths ranging from 3 to 490 µm and up to 400 visible bacterial cells deep (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation